CAMP TALK AND CITATIONALITY USED BY JACK MCFARLAND IN WILL & GRACE - Taufiq, Rizal; Nugroho, Suray Agung (ELTIN Journal, 2024)
This research investigates the use of camp talk and citationality by Jack McFarland in the U.S sitcom Will and Grace. Using the first season’s transcript of the show and thoroughly watching the whole episodes, this study utilized a qualitative method to discover where he potentially employed camp talk and citationality in his utterance, and further categorized them based on the aspect of camp talk and citationality under the theory of Harvey (2002). The findings show 10 instances were identified, including three instances of citing cultural artefacts to foster a sense of shared culture with his interlocutors, three instances of citing the linguistic medium to challenge traditional gender norms, and four instances of citing femininity to use strategies of how women communicate. Thus, the results demonstrate the vital role that language and culture play in reinforcing his gay identity, as well as the ability of language to subvert accepted norms and influence his interpersonal relationships.